2013
DOI: 10.1345/aph.1r635
|View full text |Cite
|
Sign up to set email alerts
|

Discordant aPTT and Anti-Xa Values and Outcomes in Hospitalized Patients Treated with Intravenous Unfractionated Heparin

Abstract: aPTT and anti-Xa values are frequently discordant when used to measure UFH in hospitalized patients. A disproportionate prolongation of the aPTT relative to the anti-Xa was the most common discordant pattern in our study. Patients with relatively high aPTT to anti-Xa values appear to be at increased risk of adverse outcomes. Monitoring both aPTT and Xa values may have utility in managing such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 33 publications
(23 reference statements)
2
71
1
1
Order By: Relevance
“…The main limitations of this study are the small sample size and short study period, which prevented a comprehensive investigation of risk factors for both bleeding and thrombosis complications. However, our results are consistent with previous studies in regard to bleeding complications due to discordant values while monitored with anti‐Xa protocol …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The main limitations of this study are the small sample size and short study period, which prevented a comprehensive investigation of risk factors for both bleeding and thrombosis complications. However, our results are consistent with previous studies in regard to bleeding complications due to discordant values while monitored with anti‐Xa protocol …”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that monitoring UFH infusion with the anti‐Xa compared with aPTT achieved therapeutic range more rapidly, maintained levels within the goal range for a longer time and required fewer adjustments in dosage and repeated tests . The results of recent studies have raised concern for differences between anti‐Xa and aPTT values and the increased risk of bleeding due to discordant values . Patients with supratherapeutic aPTT values compared with normal anti‐Xa values appear to be at a higher risk of adverse outcomes, such as bleeding complications and death …”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…In addition to these clinical scenarios, discordance between anti‐Xa and aPTT is common in pediatrics, as reported in this study and others . Relatively prolonged aPTT values with respect to anti‐Xa have been associated with increased bleeding events and adverse outcomes in both children and adults . Thus, anti‐Xa and aPTT assess different aspects of coagulation and heparin therapy, and both are imperfect measures of anticoagulation status with UFH treatment.…”
Section: Resultssupporting
confidence: 56%
“…In hospitalized patients who required heparin for cardiovascular indications, aPTT and antiXa levels were discordant the majority of the time; high aPTT/in-range antiXa discordance predicted major bleeding and mortality (4). In pediatric ECMO patients, lower antiXa levels (but not ACT or aPTT levels) were associated with circuit thrombosis, although hemostatic changes that occur during early life makes it difficult to generalize this observation to adults (5).…”
Section: Dear Editormentioning
confidence: 99%